2018
DOI: 10.1016/j.jacc.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasia and the Heart

Abstract: The intersection of oncological and cardiovascular diseases is an increasingly recognized phenomenon. This recognition has led to the emergence of cardio-oncology as a true subspecialty. This field is not simply limited to primary cardiac tumors or complications of chemotherapeutic medications. Rather, it also encompasses metastatic cardiovascular complications and secondary cardiovascular effects of the underlying neoplasia. This review will broadly cover primary and metastatic cardiac neoplasms, as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 153 publications
0
38
0
8
Order By: Relevance
“…In the case of secondary tumors located in the myocardium, the clinical pattern will be proportional to the degree of myocardial infiltration or in some way related to the wall infiltration site [ 6 ]. Typical presentation includes arrhythmias and conduction disturbances and complete atrioventricular blocks, especially if the conduction system has been infiltrated [ 49 ].The diagnostic evaluation is the same as that for primary cardiac tumors and relies upon echocardiography, CMR imaging, and CT to ascertain the extent of cardiac involvement. However, the method of choice to detect cardiac metastasis and their complications is echocardiography [ 34 ].…”
Section: Secondary Cardiac Tumorsmentioning
confidence: 99%
“…In the case of secondary tumors located in the myocardium, the clinical pattern will be proportional to the degree of myocardial infiltration or in some way related to the wall infiltration site [ 6 ]. Typical presentation includes arrhythmias and conduction disturbances and complete atrioventricular blocks, especially if the conduction system has been infiltrated [ 49 ].The diagnostic evaluation is the same as that for primary cardiac tumors and relies upon echocardiography, CMR imaging, and CT to ascertain the extent of cardiac involvement. However, the method of choice to detect cardiac metastasis and their complications is echocardiography [ 34 ].…”
Section: Secondary Cardiac Tumorsmentioning
confidence: 99%
“…Rarely, endocardial deposits can be seen with intracavitary growth and even rarer tumor infiltration of heart valves [8]. Although metastatic disease to the heart is believed to be underestimated, it has been reported to occur between 0.7% and 3.5% in the general population [9]. Post mortem studies have shown cardiac metastases in up to one-fourth of patients who died of malignancy, and leukemic infiltrates of the heart in a third of patients who die of leukemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tumours can be metastatic and spread via haematogenous seeding (e.g., melanoma, lymphoma), lymphatic spread (e.g., breast cancer), venous extension (e.g., renal cancer), or direct extension (e.g., lung cancer) [ 66 ]. Regardless of tumour type, any cardiac mass can have hemodynamic effects depending on the location, by impairing valvular function or obstructing normal blood flow.…”
Section: Cardio-oncology Syndrome Type V (Cos 5): Systemic and Genetic Conditionsmentioning
confidence: 99%